2016
DOI: 10.1002/jmri.25484
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI findings of sinonasal rhabdomyosarcoma in adults with comparison to carcinoma

Abstract: A multiparametric approach using conventional MRI with added ADCs had the potential to improve the diagnostic accuracy of sinonasal rhabdomyosarcoma in adults. Evidence level: 4 J. Magn. Reson. Imaging 2017;45:998-1004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Histopathologically, the tumor cells of ONBs are "small, round, blue" cells slightly larger than mature lymphocytes, with a very high nucleus‐to‐cytoplasm ratio, resulting in a low mean D value of ONBs . Recent studies have shown that other common small round cell malignant tumors, such as lymphoma and rhabdomyosarcoma, can be differentiated from SCCs by measurements of ADC values, revealing that D values of DKI may also be useful in the discrimination of ONBs and SCCs. However, we found no significant differences between these two entities, perhaps because SCC is also a common type of sinonasal malignant tumor with densely packed tumor cells, which may restrict water diffusion .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathologically, the tumor cells of ONBs are "small, round, blue" cells slightly larger than mature lymphocytes, with a very high nucleus‐to‐cytoplasm ratio, resulting in a low mean D value of ONBs . Recent studies have shown that other common small round cell malignant tumors, such as lymphoma and rhabdomyosarcoma, can be differentiated from SCCs by measurements of ADC values, revealing that D values of DKI may also be useful in the discrimination of ONBs and SCCs. However, we found no significant differences between these two entities, perhaps because SCC is also a common type of sinonasal malignant tumor with densely packed tumor cells, which may restrict water diffusion .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Jiang et al found that the kurtosis (K) value of DKI demonstrated significantly higher accuracy compared with the apparent diffusion coefficient (ADC) value for differentiating benign from malignant sinonasal lesions, suggesting that DKI may be helpful for differentiating ONBs from SCCs. By providing noninvasive morphologic and functional information of the tumor microvasculature, quantitative DCE‐MRI can be useful for discriminating malignancies from benign lesions and monitoring treatment response in the head and neck . Therefore, DKI and DCE‐MRI may be used to better evaluate and discriminate the cytostructural and hemodynamic differences that exist between ONBs and SCCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of bone destruction and intratumoral necrosis were significantly higher in rhabdomyosarcoma, which is in accordance with previous reports. 15,16 Kato et al 17 evaluated CT and MRI features of maxillary sinus ACCs. In their cohort of maxillary sinus ACCs, PNTS was an uncommon imaging finding.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The tumors may appear isointense and low signal intensity to surrounding skeletal muscle on T1-weighted MRI, high and heterogeneous signal on T2-weighted images and contrast-enhanced to variable degrees on T1-weighted sequences. [15,16] Alveolar subtypes, in particular, may show areas of hemorrhage and necrosis as well. [17] But, in the case presented here, CT of the abdomen showed a sharply defined solid-cystic mass with irregular density in retrorectal-presacral space.…”
Section: Discussionmentioning
confidence: 99%